Peranan dan Kinerja TKBM di PT. Bandar Krida Jala Patimban untuk Bongkar Muat di Pelabuhan Patimban Subang - Dharmawan, Kukuh Aditya; Akhmad, Ekka Pujo Ariesanto (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2022)
This research was carried out with the intent and purpose of knowing the role and performance of TKBM at PT. Bandar Krida Jala Patimban for loading and unloading at Patimban Port, Subang. In this study the research design uses a qualitative approach by processing data from interviews with influential people in the company. In order to mobilize and group human resources, one must know what cargo will be unloaded. This is where port operations can mobilize human resources. Because loading and unloading management is an attempt to achieve the goal of loading and unloading performance and human resources play an important role at the port, and from there management plays an important role in carrying out loading and unloading activities. PT. Bandar Krida Jala (BKJL) Patimban, as the executor of loading and unloading activities for Completely Built Up (CBU) vehicle units or vehicles sent as a whole, both Passenger Cars, Trucks, High & Heavy Equipment. The researcher analyzed the relationship between the role of loading and unloading workers (TKBM) and loading and unloading performance based on data obtained from observations, documentation and interview results from informants, the greater the factors that influence TKBM, the more it will affect the performance of loading and unloading activities. The better the role of TKBM, the better its performance in the process of loading and unloading activities, and vice versa. In this case, the company is also affected due to the unfavorable loading and unloading workforce.